Systemic Thrombolysis for Isolated Splenic Vein Thrombosis Secondary to Oral Contraceptives: A Case Report - Li Q; Wang R; Qi X (Dove Medical Press, 2024)
Qianqian Li,* Ran Wang,* Xingshun Qi Department of Gastroenterology, General Hospital of Northern Theater Command, Shenyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Xingshun Qi, Department of Gastroenterology, General Hospital of Northern Theater Command, No. 83 Wenhua Road, Shenyang, Liaoning Province, 110840, People's Republic of China, Tel +86-24-28897603, Fax +86-24-28851113, Email xingshunqi@126.comAbstract: Isolated splenic vein thrombosis (ISVT) is a very rare venous thromboembolism in the absence of pancreatic diseases, which can cause acute abdominal pain and chronic left-side portal hypertension. Herein, we reported a 40-year-old female patient who developed ISVT after taking oral contraceptives. Anticoagulation with oral rivaroxaban was the first-line choice of therapy in this case. Since then, abdominal pain alleviated, but she did not achieve vessel recanalization. Thus, a 7-day systemic thrombolysis with urokinase was given. Abdominal pain disappeared, but ISVT was not significantly improved. During follow-up period, long-term anticoagulation with oral rivaroxaban was given. Collectively, this case indicates the possibility of oral contraceptives as a risk factor of ISVT as well as anticoagulation combined with systemic thrombolysis as a choice of treatment for ISVT. Certainly, long-term follow-up is necessary in this case.Keywords: splenic vein thrombosis, oral contraceptives, anticoagulation, rivaroxaban, thrombolysis